Optimization of protease production by the fungus Monacrosporium thaumasium and its action against Angiostrongylus vasorum larvae - Filippe Elias de Freitas Soares (Revista Brasileira de Parasitologia Veterinária, 2013)
The objectives of this study were to optimize protease production from the nematophagous fungus Monacrosporium thaumasium (NF34a) and evaluate its larvicidal activity and biological stability. An isolate of the nematophagous fungus Monacrosporium thaumasium (NF34a) was used to produce the enzyme. The Plackett-Burman design was used in order to scan which components of the culture medium could have a significant influence on protease production by the fungus NF34a. An in vitro assay was also performed to evaluate the larvicidal activity of NF34a. It was observed that only one component of the culture medium (yeast extract), at the levels studied, had any significant effect (p < 0.05) on protease production. There was a reduction (p < 0.01) in the mean number of larvae recovered from the treated groups, compared with the control groups. The results confirm previous reports on the efficiency of nematophagous fungi for controlling nematode larvae that are potentially zoonotic. Thus, given the importance of biological control, we suggest that further studies should be conducted on the protease produced by the fungus Monacrosporiumthaumasium.